Oral Health in Correctional Facilities: A Study on Knowledge, Attitude and Practice of Prisoners in Benghazi central Prison - Shalloof, Ahmed Fathi (faculty of Basic Medical Science - Libyan International Medical University, 2018)
The prisoners represent a population group that is disadvantaged, socially deprived underprivileged and needs immediate attention in regards to provision of necessary oral health care, health promotion and motivation, tobacco cessation. A cross-sectional study was conducted in Benghazi central prison (Al-Kwifiya) sample of 358 prisoners. 38.3% of the prisoners were aware that tooth brushing helps in preventing gum diseases. 85.8% reported that they had some or the other dental problems during their stay in the jail. A majority of the prisoners (57.8%) reported consuming tobacco can cause gum disease. 54.8% prisoners never consulted a dentist. 71.8% prisoners did not get proper dental treatment for their problem. When inquiring the form of tobacco being used 27.1% reported of smoking, 37.7% used tobacco only in the chewable form and 32.7% were indulged in consuming tobacco in both forms i.e. smoked as well as chewed. 18.7% were bidi smokers and 81.3% were into cigarette smoking. Prisoners form the isolated and weaker sections of the society, but it is the responsibility of every health care worker to serve them as the incarceration period can give an ideal opportunity to improve and promote good oral health. An urge persist for the development of a basic oral health care package that for all inmates
Health is a fundamental human right. Oral health has been considered as the mirror of general health by Sir William Osler and is recognized as important as the general health (1) . An individual’s health is governed by a wide variety of factors which may include congenital, hereditary, environmental and behavioral factors; the behavioral and environmental factors are most crucial in promotion and maintenance of the oral health of the people too. The high prevalence of dental diseases, apart from leading to ill effects on the health of the people afflicted, also causes economic loss and significant absenteeism (1) . Keeping in consideration their high prevalence and incidence, oral diseases tend to qualify as a major public health problem in all parts of the world. Because of the high costs of dental treatment, they mostly affect the underprivileged and socially deprived population. In Libya, dental caries experience and distribution remains high and skewed in all age groups and increases as the age advances. Secondly, the prevalence of components of periodontal disease (bleeding, calculus, pockets) was found to be as high as 83%. Also tobacco consumption in any form has shown to have detrimental effects on oral health and is an established causative factor for oral cancer